STUDENTS PERCEPTIONS OF E-LEARNING FOR ESL/EFL IN SAUDI UNIVERSITIES AT TIME OF CORONAVIRUS: A LITERATURE REVIEW - Khaled Layali; Ahmed Al-Shlowiy (Universitas Kuningan, 2020)
Coronavirus (COVID-19) was declared a world pandemic by the World Health Organization (WHO) on January 30, 2020. As a safety measure to protect people, most governments in the world, including Saudi Arabia, decided to close universities and workplaces. Prompted by this shut down, the researchers aimed to review the students perceptions of e-learning for ESL/EFL in Saudi universities at this Coronavirus time. As such, this review reported on four primary studies that were found relevant to its focus during the period from January 2020 till April 2020 (Abu-Ayfah, 2020; Ahmad, 2020; Alshehri & Cumming, 2020; Hakami, 2020). As a historical perspective of the reviews focus, it also reported on other four primary studies dating back to 2018 and 2019 (Alshehri, Rutter & Smith, 2019; Mutambik, 2018; Oyaid & Alshaya, 2019; Sharma, 2019). The reviews objectives were to report: 1) students perceptions of e-learning for ESL/EFL, 2) benefits of e-learning for ESL/EFL, and 3) drawbacks of e-learning for ESL/EFL in Saudi universities. Moreover, this review was compared to a conference paper from China (He, 2020) as it presented a strategy to continue college English learning and teaching at Coronavirus time. Results showed students positive views, many benefits and limited drawbacks of e-learning for ESL/EFL in Saudi universities. Keywords: e-learning; ESL/EFL; students perceptions; benefits and drawbacks; Saudi education.